2019
DOI: 10.3390/molecules24071398
|View full text |Cite
|
Sign up to set email alerts
|

Tests on Material Compatibility of Phase Change Materials and Selected Plastics

Abstract: Practical applications of Phase Change Materials (PCMs) often require their encapsulation in other materials, such as metals or plastics. This raises the issue of compatibility between PCMs and encapsulating materials, which has still not been sufficiently addressed. The study presented here follows existing research and provides experimental evaluation of the suitability of selected PCMs for proposed integration in building structures. Two organic PCMs, two inorganic PCMs and three representative plastics (po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The idea of its application in the Central European climate is to replace heavy-weight structures with light-weight structures with enhanced heat storage capacity by integrated bio-based PCMs. The experiment is based on the gravimetric analysis which is generally recommended for the evaluation of the most suitable combination of PCMs and material for encapsulation [6]. Four types of plastics were selected for the test of their compatibility with bio-based PCM Coconut oil:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of its application in the Central European climate is to replace heavy-weight structures with light-weight structures with enhanced heat storage capacity by integrated bio-based PCMs. The experiment is based on the gravimetric analysis which is generally recommended for the evaluation of the most suitable combination of PCMs and material for encapsulation [6]. Four types of plastics were selected for the test of their compatibility with bio-based PCM Coconut oil:…”
Section: Methodsmentioning
confidence: 99%
“…Generally, PCMs must be encapsulated and hermetically sealed because the leakage of storage medium and undesirable integration with building materials and indoor environment must be avoided. Encapsulation means shelling the PCMs with suitable coating material [6]. The material of encapsulation ensures heat transfer, thermal and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Selecting materials that are chemically stable, corrosion-resistant, and can accommodate PCM volume changes is vital for the reliable and efficient operation of PCM-based systems. Proper compatibility ensures enhanced PCM reliability and addresses issues arising from interactions with additives and adjacent materials, preventing PCM degradation and ensuring system longevity [82].…”
Section: Issues Of Materials Compatibility With Pcmsmentioning
confidence: 99%
“…Strategies like corrosion-resistant coatings and the exploration of innovative container materials, including composites and polymers, have improved resistance to chemical reactions and corrosion. Life cycle assessments and computational modeling have furthered the understanding of PCM behavior and system design, promoting more sustainable and efficient PCM solutions [82,86].…”
Section: Recent Findings On Materials Interactions With Pcmmentioning
confidence: 99%
“…Generally, medium-sized or full-sized environmental chambers are used to simulate the environment such as wind, sunshine and rain to study the thermodynamic properties of building basic materials, building envelopes and protective materials. [114][115][116][117][118] In addition, those environmental chambers with two adjacent cabins that can create indoor and outdoor environments at the same time are usually used to study the thermal and moisture properties of walls. Through the above studies, we found that thermal physical property parameters can be improved by studying the changing of the material composition, volume, production techniques, environmental parameters, etc., using environmental chambers.…”
Section: Contentmentioning
confidence: 99%